Characterization of Gutta Percha and Its Application as Plywood Adhesive - Tati Karliati; Fauzi Febrianto; Wasrin Syafii; Imam Wahyudi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
Gutta percha resin is a biodegradable and renewable elastomer trans-1,4- isoprene rubber and obtained from Palaquium tree through extraction of leaf or tapping of stem. The purposes of this research were to characterize the gutta percha and its application for wood (plywood) adhesive. Characteristics of gutta percha evaluated in this experiment were moisture content (MC), density, ash content, melting and decomposition temperatures. Plywood performance were evaluated under SNI 01-50019.10-2001 standard. Four different glue spread i.e.,175, 200, 225 and 250 g m-2 were introduced in this experiment. Five percent of maleic anhydride (MAH) and 1% of benzoyl peroxide (BPO) were used as a modifier and an initiator, respectively. The result showed that gutta percha has white to creamy color. The density, MC and ash content of gutta percha were 1.01 g cm-3, 6.09%, and 0.074% respectively. The melting and decomposition temperatures of gutta percha were noted 72.6°C and 482.2°C, respectively. Modification of gutta percha with 5% MAH enhanced the shear strength of resulted plywood. Modified gutta percha with 5% MAH in absence of BPO with glue spread of 250 g.cm-2 can be used for interior and exterior plywood adhesive. Their shear strength value fulfilled the requirement of SNI 01-5008.2-1999 standard.Key words : benzoil peroxide, glue spread gutta percha, maleic anhydride, plywood, wood adhesive